Broadband tunable terahertz plasmon-induced transparency in Dirac semimetals. (August 2018) - Chen, Huan; Zhang, Huiyun; Zhao, Yunkun; Liu, Shande; Cao, Maoyong; Zhang, Yuping
Highlights: Novel 3D Dirac semimetal was used as a platform to design a PIT system. The bandwidth of the PIT window can be broadened by adjust the structural parameter. The PIT window can be tuned without refabricating the structures. A higher FoM value was obtained in our design. Abstract: In this paper, we present a numerical and theoretical study on the realization of the tunable plasmon-induced transparency (PIT) effect at terahertz (THz) frequencies in Dirac semimetal (known as "three-dimensional graphene") metamaterials. The simulations reveal that the PIT effect is generated because of the excitation of the dark mode that can be regarded as a dipole. Further investigation reveals that the bandwidth can be broadened while the resonant frequencies of the PIT remain unchanged. At the same time, the resonant frequency of the PIT window can be dynamically tuned by changing the Fermi energy of the Dirac semimetals instead of refabricating the structures. Moreover, a figure of merit value of about 10.55 is achieved in our proposed design based on the performed sensitivity measurement. Our study can provide guidance for various THz devices in practical applications.